P065: The history of emergency medicine in Ottawa. (15th May 2017) - James, D.; Lamb, S.; Frank, J.R.
Abstract : Introduction/Innovation Concept: There is a paucity of peer-reviewed works investigating the History of Emergency Medicine (EM) in Canada, and none examining a single centre. This study analyzed the academic and clinical evolution of EM in the City of Ottawa from its origins to present.Methods: The study comprised primary and secondary historical research and an oral history methodology. A literature review was performed on the following databases: PubMed, Medline, EMBASE, JSTOR, Web of Science, Historical Abstracts; five medical history journals were also searched. Data were collected from City of Ottawa Archives, Archives of the Sisters of Charity of Ottawa, The Ottawa Hospital Libraries, University of Ottawa Libraries, RCPSC and CFPC Archives, Historical Society of Ottawa documents, Ottawa newspaper archives, and professional correspondences. The oral history component consisted of formal interviews with seven practicing and retired Emergency Physicians in Ottawa. Ethics approval was not required though consent was obtained from respondents.Curriculum, Tool, or Material: The literature review yielded the following: PubMed: 218 results, 180 excluded for non-relevance, 3 papers included in analysis. Historical Abstracts: 1 result, overlap with PubMed. Other databases and medical history journals yielded no papers. Along with extensive archival data, these results were used to construct a detailed timeline of EM history in Ottawa and Canada more broadly. Residency training in EM in Ottawa was initiated in 1972 at the impetus of the Board of the Ottawa Civic Hospital. Two main themes recurred in the interviews: resistance from existing specialties to EM becoming a specialty, and early Emergency Rooms staffed by the least trained people treating the least differentiated patients. Early EM physicians were not viewed positively by other specialists.Conclusion: Pioneering EM physicians were forced to validate the specialty as distinct, rigorous, and credible. In Ottawa this was achieved by developing strong core academics and research. Nationally, this has been instrumental in establishing EM as a viable standalone academic specialty. Modern consult pushback may have evolved from existing specialists fighting against the creation of EM combined with their negative perception of EM physicians. These data could be incorporated into learning modules for EM residency academic programs, and the methods applied to other centres.